Comparison of Acidity Degree (pH) on Thrombocyte Concentrate Products: Apheresis Method and Pooling Method - Ariani, Resti; Kuspranoto, Abdul H; Aulia, Intan (POLTEKKES KEMENKES BENGKULU, 2021)
One indicator of the decreasing quality of thrombocyte concentrate (TC) during storage is the pH value. Thrombocyte making can use pooling and apheresis methods. The pooling method is carried out by combining 4-6 bags of single thrombocytes with sterile connecting device, while apheresis method is done automatically using apheresis machine. Quality Control Inspection of TC product is conducted to ensure the quality of the product in accordance with applicable specifications. This study aims to find out the difference in acidity degree value (pH) in thrombocyte concentrate apheresis and pooling methods. This type of research is descriptive comparative with the design of cross sectional section study. The population of research was all the results of pH value examination on thrombocyte apheresis and pooling in UDD PMI Semarang city in 2020, with the number of 48 bags each. The sampling technique used is total sampling. Analysis of research data was conducted univariate and bivariate with the help of SPSS version 25. The average pH value in thrombocyte apheresis 7,145 and in thrombocyte pooling 7,417. Bivariate analysis of thrombocyte apheresis and pooling using Independent Sample T-Test has a significance value of 0.000. From the results of the analysis of research data, there is a significant difference between the pH value in thrombocytes apheresis and pooling method. Because there are differences between the two pH values in thrombocyte products, there needs to be an improvement in the evaluation and monitoring of each product.